(untitled) (KONFERENSIYA, 2025)
This article explores the formation of ecological terminology, its linguistic characteristics, origins, and the theoretical and practical challenges encountered in translating ecological texts. Due to the rapid development of ecology as a science, new scientific terms emerge every year, and the expansion of international scientific cooperation makes the accurate translation of these terms essential. The article scientifically analyzes the interdisciplinary nature of ecological terminology, its polysemy, the critical role of context in translation, and the need to standardize terminology used by international organizations. Furthermore, semantic distortions, stylistic inconsistencies, and methodological shortcomings frequently encountered in ecological text translation are explained with examples. The study emphasizes that accurate translation of ecological terms plays a crucial role in environmental policy, scientific research, ecological education, and the formation of environmental awareness.